Mukhamandapa of the Matha - Temples of India Project Team (Jio Institute, 2024)
Seen here are the details of the mukhamandapa (front porch) of the matha (monastic or residential building) of the Suhaveshwar Temple. The entrance of the mukhamandapa is flanked by two walls which must have had kakshasanas (seat backs) above it. The corners are marked by pillars. In front of the mukhamandapa is an enclosed space that might have been used as a shrine of the matha. The pillars of the matha are plain, made up of rectangular stone slats with minimal ornamentation.